Degranulation of human mast cells: modulation by P2 receptors’ agonists - Schulman, Edward S.; Nishi, Haruhisa; Pelleg, Amir (Frontiers in Immunology, 2023)
Since the late 1970s, there has been an alarming increase in the incidence of asthma and its morbidity and mortality. Acute obstruction and inflammation of allergic asthmatic airways are frequently caused by inhalation of exogenous substances such as allergens cross-linking IgE receptors expressed on the surface of the human lung mast cells (HLMC). The degree of constriction of human airways produced by identical amounts of inhaled allergens may vary from day to day and even hour to hour. Endogenous factors in the human mast cell (HMC)’s microenvironment during allergen exposure may markedly modulate the degranulation response. An increase in allergic responsiveness may significantly enhance bronchoconstriction and breathlessness. This review focuses on the role that the ubiquitous endogenous purine nucleotide, extracellular adenosine 5’-triphosphate (ATP), which is a component of the damage-associated molecular patterns, plays in mast cells’ physiology. ATP activates P2 purinergic cell-surface receptors (P2R) to trigger signaling cascades resulting in heightened inflammatory responses. ATP is the most potent enhancer of IgE-mediated HLMC degranulation described to date. Current knowledge of ATP as it relates to targeted receptor(s) on HMC along with most recent studies exploring HMC post-receptor activation pathways are discussed. In addition, the reviewed studies may explain why brief, minimal exposures to allergens (e.g., dust, cat, mouse, and grass) can unpredictably lead to intense clinical reactions. Furthermore, potential therapeutic approaches targeting ATP-related enhancement of allergic reactions are presented.